Undercover operation: Belowground insect herbivory modifies systemic plant defense and repels aboveground foraging insect herbivores - Thompson, Morgan N.; Grunseich, John M.; Marmolejo, Laura O.; Aguirre, Natalie M.; Bradicich, Pius A.; Behmer, Spencer T.; Suh, Charles P.-C.; Helms, Anjel M. (Frontiers in Ecology and Evolution, 2022)
Plants attacked by insects may induce defenses locally in attacked plant tissues and/or systemically in non-attacked tissues, such as aboveground herbivory affecting belowground roots or belowground herbivory modifying aboveground tissues (i.e., cross-compartment systemic defense). Through induced systemic plant defenses, above- and belowground insect herbivores indirectly interact when feeding on a shared host plant. However, determining the systemic effects of herbivory on cross-compartment plant tissues and cascading consequences for herbivore communities remains underexplored. The goal of this study was to determine how belowground striped cucumber beetle (Acalymma vittatum) larval herbivory alters aboveground zucchini squash (Cucurbita pepo subsp. pepo) defenses and interactions with herbivores, including adult cucumber beetles and squash bugs (Anasa tristis). To explore this question, field and laboratory experiments were conducted to compare responses of aboveground herbivores to belowground larvae-damaged plants and non-damaged control plants. We also characterized changes in defensive chemicals and nutritional content of aboveground plant structures following belowground herbivory. We discovered belowground herbivory enhanced aboveground plant resistance and deterred aboveground foraging herbivores. We also found that larvae-damaged plants emitted higher amounts of a key volatile compound, (E)-β-ocimene, compared to non-damaged controls. Further investigation suggests that other mechanisms, such as plant nutrient content, may additionally contribute to aboveground herbivore foraging decisions. Collectively, our findings underscore connections between above- and belowground herbivore communities as mediated through induced systemic defenses of a shared host plant. Specifically, these findings indicate that belowground larval herbivory systemically enhances plant defenses and deters a suite of aboveground herbivores, suggesting larvae may manipulate aboveground plant defenses for their own benefit, while plants may benefit from enhanced systemic defenses against multi-herbivore attack.